(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
"Garib-oshik" is a lyrical-epic epic of the Karakalpak people, which tells about the collection of versions of the epic from the population and the recording of jiravs and bakhshis. The publication of the epic and the performance of the baxshi jirovs are studied.